2005
DOI: 10.1017/s1537592705570257
|View full text |Cite
|
Sign up to set email alerts
|

The Invention of the United States Senate

Abstract: The Invention of the United States Senate. By Daniel Wirls and Stephen Wirls. Baltimore: Johns Hopkins University Press, 2004. 288p. $49.95 cloth. $18.95 paper.In a meeting in Moscow some years ago, the former Soviet Union's principal Americanologist, Georgi Arbatov, complained to me quite seriously, “We study your system, and we still do not know how it works.” Probably one reason for Arbatov's expressed puzzlement had to do with the role played in the American governmental system by the United States … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Nevertheless, some low-income households may still need further subsidies to reduce their rent burdens, since we found that increased savings did not dramatically reduce rent burden. The Rent Relief Act of 2018, sponsored by then-Senator Kamala Harris (2018), serves as a template for such subsidies: low-income renters could receive tax credits on rent paid in excess of 30 percent of their income. Targeted, means-tested subsidies for specific populations are easy to implement “because local governments already have the infrastructure in place to administer direct cash subsidies” (NYU Furman Center 2021:6).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some low-income households may still need further subsidies to reduce their rent burdens, since we found that increased savings did not dramatically reduce rent burden. The Rent Relief Act of 2018, sponsored by then-Senator Kamala Harris (2018), serves as a template for such subsidies: low-income renters could receive tax credits on rent paid in excess of 30 percent of their income. Targeted, means-tested subsidies for specific populations are easy to implement “because local governments already have the infrastructure in place to administer direct cash subsidies” (NYU Furman Center 2021:6).…”
Section: Discussionmentioning
confidence: 99%
“…A extensão ou a profundidade dessa zona depende das condições geoclimáticas da região (Chen, 1975;Ferreira, 1995;Jones & Jefferson, 2012). Método de melhoramento para solo expansivo também referido como estabilização do solo pode ser definido como um processo físico, físico-químico ou mecânico, destinado a neutralizar a expansão, manter a estabilidade, reduzir a compressibilidade, melhorar as propriedades de engenharia, limitar a capacidade de absorção de água e reduzir a capacidade de contrair do solo tratado (Harris, 2005).…”
Section: Melhoramento De Solos Expansivosunclassified